Wait till next year : a memoir - Goodwin, Doris Kearns (New York : Simon & Schuster, 1997)
An eccentric cast of characters populates the autobiography of a young girl who roots for the Brooklyn Dodgers with her father, while her mother suffers from a debilitating illness.
Keywords: Goodwin, Doris Kearns -- Childhood and youth; Brooklyn Dodgers (Baseball team) -- History; Baseball fans -- United States -- Biography; Historians -- United States -- Biography